Three dimensional numerical solution for the bending study of magneto-piezo-elastic spherical and cylindrical shells - Monge J.C. (2021)
This paper was written in the context of the project: “Desarrollo de materiales avanzados para el diseño de nuevos productos y servicios tecnológicos para la minería Peruana” founded by CONCYTEC (FONDECYT and GRUPO BANCO MUNDIAL) under the contract number N° 032-2019-FONDECYT-BM-INC.INV. The authors of this manuscript appreciate the financial support from the Peruvian Government.